Visceral oxidative stress during antegrade cerebral perfusion and lower body circulatory arrest. Issue 4 (4th July 2019) - Ünal, Ertekin Utku; Kubat, Emre; Soran Türkcan, Başak; Kiriş, Erman; Demir, Aslı; Aytekin, Bahadır; Akkaya, Boğaçhan; Aksu, Uğur; Aksöyek, Ayşen
Abstract: Background: Antegrade cerebral perfusion (ACP) is the standard neuroprotection method in aortic surgery. Visceral ischemia during this modality brings out some controversies. We aimed to investigate the level of oxidative stress at the lower part of body during ACP. Methods: Thirty consecutive patients underwent elective ascending aorta and hemiarch repair with ACP (without distal perfusion) were enrolled to study. The patients were enrolled into two groups which were based on 50th percentile of ACP duration (15 patients in each group). Blood samples from inferior vena cava at the end of ACP were collected to assess oxidative stress with biochemical parameters such as lactate, advanced oxidative protein products (AOPP) and thiol levels. Clinical follow-up parameters regarding to visceral and spinal cord ischemia were recorded. There were no clinical complications at both groups. Results: Mean ACP duration for the study group was found to be 15 min (10–28 min). Lactate, AOPP, and thiol levels were found to be similar between two groups. Furthermore, correlation analysis revealed only low level of correlation between ACP duration and lactate levels. Renal and liver function tests were found to be similar between groups. Conclusions: Immediate parameters (such as lactate, AOPP, and thiol) that show alterations in response to oxidative stress were not affected by the duration of ACP. Therefore, ACP without distal perfusion may not be harmful when conducted for short duration.